Low Educational Attainment is a Predictor of Adverse Outcomes in Patients With Coronary Artery Disease. Issue 17 (3rd September 2019) - Kelli, Heval M.; Mehta, Anurag; Tahhan, Ayman S.; Liu, Chang; Kim, Jeong Hwan; Dong, Tiffany A.; Dhindsa, Devinder S.; Ghazzal, Bahjat; Choudhary, Muaaz K.; Sandesara, Pratik B.; Hayek, Salim S.; Topel, Matthew L.; et al.
Abstract : Background: Educational attainment is an indicator of socioeconomic status and is inversely associated with coronary artery disease risk. Whether educational attainment level (EAL) among patients with coronary artery disease influences outcomes remains understudied. Methods and Results: Patients undergoing cardiac catheterization had their highest EAL assessed using options of elementary/middle school, high school, college, or graduate education. Primary outcome was all‐cause mortality and secondary outcomes were a composite of cardiovascular death/non‐fatal myocardial infarction and non‐fatal myocardial infarction during follow‐up. Cox models adjusted for clinically relevant confounders were used to analyze the association of EAL with outcomes. Among 6318 patients (63.5 years, 63% men, 23% black) enrolled, 16%, 42%, 38%, and 4% had received graduate or higher, college, high school, and elementary/middle school education, respectively. During 4.2 median years of follow‐up, there were 1066 all‐cause deaths, 812 cardiovascular deaths/non‐fatal myocardial infarction, and 276 non‐fatal myocardial infarction. Compared with patients with graduate education, those in lower EAL categories (elementary/middle school, high school, or college education) had a higher risk of all‐cause mortality (hazard ratios 1.52 [95% CI 1.11–2.09]; 1.43 [95% CI 1.17–1.73]; and 95% CI 1.26 [1.03–1.53], respectively). Similar findings were observed for secondary outcomes. Conclusions: Low educational attainment is an independent predictor of adverse outcomes in patients undergoing angiographic coronary artery disease evaluation. The utility of incorporating EAL into risk assessment algorithms and the causal link between low EAL and adverse outcomes in this high‐risk patient population need further investigation.